Application Profile for Machine-Actionable Data Management Plans. (26th October 2021) - Miksa, Tomasz; Walk, Paul; Neish, Peter; Oblasser, Simon; Murray, Hollydawn; Renner, Tom; Jacquemot-Perbal, Marie-Christine; Cardoso, João; Kvamme, Trond; Praetzellis, Maria; Suchánek, Marek; Hooft, Rob; et al.
This paper presents the application profile for machine-actionable data management plans that allows information from traditional data management plans to be expressed in a machine-actionable way. We describe the methodology and research conducted to define the application profile. We also discuss design decisions made during its development and present systems which have adopted it. The application profile was developed in an open and consensus-driven manner within the DMP Common Standards Working Group of the Research Data Alliance and is its official recommendation.